Pengalihan Status Kepemilikan Wakaf Dibawah Naungan Yayasan Berdasarkan Undang Undang No. 41 Tahun 2004 Tentang Wakaf Dan Undang Undang No. 16 Tahun 2001 Tentang Yayasan Menjadi Aset Pribadi Dalam Perspektif Kompilasi Hukum Islam - Misna Misna (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2018)
The existence of the Foundation in managing Wakaf should play a very important social economic role in Islamic history, waqf serves as a source of funding for the economic interests of the people such as educational, religious, health and other public facilities. Based on this, the purpose of this study is to know and understand the ownership status of Foundation assets in the form of waqf which were initially managed for the benefit of the people or the community into personal assets, and to know and understand the existence of Wakaf managed by the Foundation in Indonesia. Therefore the research that will be elaborated can be identified as how should the ownership status of Foundation assets in the form of Wakaf so that it is truly managed for the benefit of the people should not become a personal asset and know how the Wakaf is managed by the Foundation in Indonesia. Research applies normative legal methods (juridical research), namely research that examines legal issues from the point of view of law in depth to the established legal norms. Analytical descriptive research specification method. The study found, first, the ownership status of Foundation assets in the form of Wakaf which was initially managed for the benefit of the people or the community into personal assets must be returned to the original owner, namely the Foundation's assets , with intensive and continuous supervision so that Wakaf managed by the Foundation is the existence of waqf that can really be optimized for the welfare of the people or the community as a whole and complex, not making Wakaf as a tool for the personal and group interests of certain foundations.